2017
DOI: 10.9790/2380-1007028185
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement Level of Extension Agent in Activities Based on Rice Check Technology at IADA PEKAN Pahang, Malaysia

Abstract: Rice is a staple food for Malaysian and productivity must be focus upon in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…From the results above, all PIME skills were at a high level which means that the extension agents have a high level of skills in planning, implementing, monitoring and evaluating during MCO. Nevertheless, there is a study that contradicted the result of this research, which stated that monitoring showed a moderate level but it is still a vital skill that can make sure all the information and knowledge transferred to the farmers can be used effectively (Yusuf et al, 2017). Furthermore, the performance of the extension agent also was a high level, same as stated by Olagunju et al (2021) that the performance of extension agent was high before the MCO.…”
Section: Level Of Program Development Skills and Work Performancementioning
confidence: 59%
“…From the results above, all PIME skills were at a high level which means that the extension agents have a high level of skills in planning, implementing, monitoring and evaluating during MCO. Nevertheless, there is a study that contradicted the result of this research, which stated that monitoring showed a moderate level but it is still a vital skill that can make sure all the information and knowledge transferred to the farmers can be used effectively (Yusuf et al, 2017). Furthermore, the performance of the extension agent also was a high level, same as stated by Olagunju et al (2021) that the performance of extension agent was high before the MCO.…”
Section: Level Of Program Development Skills and Work Performancementioning
confidence: 59%
“…This is best describing the situation that happens and might support the results of this study. However, even though monitoring contributes a moderate level towards the level of readiness, it is still a vital skill to make sure all the information and knowledge can be transferred to the farmers effectively (Yusuf et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This skill is important to give the result that can determine the achievement of the extension agent development program as a whole. Monitoring also is a vital skill in order to make sure knowledge about the progress, and the effect on outcomes whether it is implemented effectively or not (Yusuf et al, 2017).…”
Section: Introductionmentioning
confidence: 99%